2004
DOI: 10.1121/1.1690076
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of missing fundamental versus spectrally cued pitch: Individual differences for complex tones with unresolved harmonics

Abstract: In a two-alternative, forced-choice experiment, subjects had to compare the pitches of two sounds, A and B. Each sound was composed of four successive harmonics of a fundamental frequency between 100 to 250 Hz, added in cosine or Schröder phase. The harmonic frequencies of A were lower than those of B; the missing fundamental frequency of A was higher than that of B. The dominance of the missing fundamental versus the spectrally cued pitch--a pitch percept corresponding to spectral components--was measured as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This meant that, when F0 was changed, spectral cues were available. Subjects might have based judgments on the frequency of the lowest or highest harmonic, or, when harmonics were unresolved, on shifts in the spectral center of gravity (or excitation pattern) of the stimuli (Moore and Moore, 2003a;Renken et al, 2004). Moore and Moore (2003a) showed that F0DLs for hearing-impaired subjects were often markedly larger when such spectral cues were eliminated than when they were present.…”
Section: Introductionmentioning
confidence: 98%
“…This meant that, when F0 was changed, spectral cues were available. Subjects might have based judgments on the frequency of the lowest or highest harmonic, or, when harmonics were unresolved, on shifts in the spectral center of gravity (or excitation pattern) of the stimuli (Moore and Moore, 2003a;Renken et al, 2004). Moore and Moore (2003a) showed that F0DLs for hearing-impaired subjects were often markedly larger when such spectral cues were eliminated than when they were present.…”
Section: Introductionmentioning
confidence: 98%
“…The strong contribution of auditory cortex suggests that fundamental pitch sensations might be subject to learning-induced neural plasticity. Indirect evidence for this assumption comes from psychoacoustic studies, which show that the perceived salience of the F0 does not depend only on the stimulus spectrum but also on the individual listener (Houtsma & Fleuren, 1991; Renken, Wiersinga-Post, Tomaskovic, & Duifhuis, 2004; Singh & Hirsh, 1992; Smoorenburg, 1970). Surprisingly, the authors of these studies did not address the reasons for the observed interindividual variations.…”
mentioning
confidence: 99%
“…Previous studies of effects of the missing fundamental have established that listeners often attribute manipulations that simultaneously produce changes in overall spectral envelope shape and spectral centroid to changes in pitch (Renken et al, 2004; Seither-Preisler et al, 2007; Vurma, Raju, & Kuuda, 2011). However, we believe this study is unique in directly equating spectral centroids across a tone pair, and comparing judgments of centroid-equated pairs to non-centroid-equated pairs.…”
Section: Discussionmentioning
confidence: 99%
“…As with the other interactions of timbre and pitch mentioned above, the degree to which listeners hear pitch as unchanged after the removal of F 0 reflects strong individual differences, and those differences have been found to correlate with musical training. Renken, Wiersinga-Post, Tomaskovic, and Duifhuis, (2004) found that the degree to which perceived pitch was influenced by the (missing) fundamental, rather than the spectral components of a tone, varied considerably across listeners. Furthermore, musically trained listeners are more likely to respond to the (missing) F 0 than are untrained listeners.…”
mentioning
confidence: 97%